2022
DOI: 10.1186/s12872-022-02553-5
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically healthy versus unhealthy obese phenotypes in relation to hypertension incidence; a prospective cohort study

Abstract: Background Although obesity increases the risk of hypertension, the effect of obesity based on metabolic status on the incidence of hypertension is not known. This study aimed to determine the association between obesity phenotypes including metabolically unhealthy obesity (MUO) and metabolically healthy obesity (MHO) and the risk of hypertension incidence. Methods We conducted a prospective cohort study on 6747 adults aged 35–65 from Ravansar non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
(41 reference statements)
1
0
0
Order By: Relevance
“…Moreover, the risk was greater for those with metabolic unhealthiness than in baseline exposure models. Consistent with a previous study, 31 individuals with MHO demonstrated healthier behaviours, were more educated, and were younger. However, among individuals who had MHO at baseline and transitioned to MUO within 2 years, higher baseline levels of triglycerides, HDL cholesterol and glucose were observed.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the risk was greater for those with metabolic unhealthiness than in baseline exposure models. Consistent with a previous study, 31 individuals with MHO demonstrated healthier behaviours, were more educated, and were younger. However, among individuals who had MHO at baseline and transitioned to MUO within 2 years, higher baseline levels of triglycerides, HDL cholesterol and glucose were observed.…”
Section: Discussionsupporting
confidence: 90%
“…The association between obesity and IR has already been established [29]. Metabolically unhealthy obesity (MUO) has also been observed to be associated with IR and hypertension [29,30]. Okura et al 's study in the Japanese population showed that BMI ≥ 23 is a risk factor for IR [31].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 20% of the entire adult population of the world will be obese by 2030 [1]. Obesity increases glucose levels and worsens lipid profiles, blood pressure, and the incidence of inflammation [2][3][4]. Consequently, this condition is associated with the worsening of almost all cardiovascular risk factors such as hypertension, type 2 diabetes (T2DM), metabolic syndrome, dyslipidemia, and chronic kidney disease (CKD).…”
Section: Introductionmentioning
confidence: 99%